Future-past asymmetries, evidential grounding, and projection - Cariani, Fabrizio (Proceedings of the Amsterdam Colloquium, 2022)
I develop a lexical solution to some important puzzles recently discovered by Ninan (forthcoming), which highlight striking asymmetries between future- and past-directed talk.